Avaliação Diagnóstica do Programa de Apoio a Projetos de Extensão do Instituto Federal de Educação, Ciência e Tecnologia do Ceará. - Castro, André Monteiro de (2019)
The Extension Projects Support Program (Papex) was created by the Office of Extension of the Federal Institute of Education, Science and Technology of Ceará (IFCE) with the objective of strengthening extension in the major thematic areas, defined according to the National Policy of Extension (PNE) 2011-2020. Thus, it is expected that Papex will be promoting the development of projects that contribute to the extension of the project to obtain good results when evaluated under the areas defined in the PNE: management; academic plan; university-to-society relationship and academic production. Therefore, this study aimed to evaluate the results of the (Papex), using indicators elaborated by the Forum of Pro-Rectors of Extension of the Brazilian Public Universities (Forproex). To reach the objective, a qualitative-quantitative research was used, using a descriptive study, having the primary data collected through a questionnaire, and the secondary data through documentary research. The results were evaluated through a comparison between the data obtained and the indicators of the Brazilian Indicators of University Extension (IBEU), comparative study, with the inclusion of tables and graphs. Thus, 55 coordinators of Papex projects from all its 5 editions, all of them teachers or administrative staff of the IFCE participated in the study, a large majority, 89.1%,of the teachers' class. Therefore, in the scope of the management, it is necessary to rethink the allocation of resources and the monitoring of the projects. Within the scope of the academic plan, it was verified that Papex is providing a strong approximation between the extension of teaching and research. In the relation between university and society, the priority attention to the public in situations of vulnerability stands out. In relation to academic production, it is noticed the need for greater elaboration of audio-visual products and artistic materials. It is concluded, therefore, that Papex is reaching its goal of strengthening the extension in the IFCE, reaching good indexes in indicators elaborated by Forproex.